Ossifying fibroma of nasal cavity: A rare case report - Kumar, Vinod; Kanaujia, Surendra Kumar; Gautam, Harendra Kumar; Mani, Dewal (Indian Journal of Case Reports, 2018)
Ossifying fibroma (OF) is considered a rare benign fibro-osseous lesion that occurs most commonly in female patients. It mainly involves the mandibular and maxillary bones, although in rare cases, it may develop within the nasal cavity. Here, we present a rare case report of OF of the nasal cavity in a 30-year-old female. OF is usually diagnosed by histopathological examination and treated by enucleation. However, larger lesions require radical resection.